Effect of Acupuncture on Postoperative Ileus after Distal Gastrectomy for Gastric Cancer - Jung, Se Yun (J Gastric Cancer, 2017)
PURPOSE: Acupuncture has recently been accepted as a treatment option for managing postoperative ileus (POI) and various functional gastrointestinal disorders. Therefore, we conducted a prospective randomized study to evaluate the effect of acupuncture on POI and other surgical outcomes in patients who underwent gastric surgery. MATERIALS AND METHODS: Thirty-six patients who underwent distal gastrectomy for gastric cancer from March to December 2015 were randomly assigned to acupuncture or non-acupuncture (NA) groups at 1:1 ratio. The acupuncture treatment was administered treatment once daily for 5 consecutive days starting at postoperative day 1. The primary outcome measure was the number of remnant sitz markers in the small intestine on abdominal radiograph. The secondary outcome measure was the surgical outcome, including the times to first flatus, first defecation, start of water intake, and start of soft diet, as well as length of hospital stay and laboratory findings. RESULTS: The acupuncture group had significantly fewer remnant sitz markers in the small intestine on postoperative days 3 and 5 compared to those in the NA group. A significant difference was observed in the numbers of remnant sitz markers in the small intestine with respect to group differences by time (P<0.0001). The acupuncture group showed relatively better surgical outcomes than those in the NA group, but the differences were not statistically significant. CONCLUSIONS: In this clinical trial, acupuncture promoted the passage of sitz markers, which may reflect the possibility of reducing POI after distal gastrectomy.